Psychological and physical impact of urban green spaces on outdoor thermal comfort during summertime in The Netherlands - Klemm, Wiebke; Heusinkveld, Bert G.; Lenzholzer, Sanda; Jacobs, Maarten H.; Van Hove, Bert (Building and environment, 2015)
Green infrastructure can improve thermal comfort in outdoor urban spaces in moderate climates. The impact of green spaces on thermal comfort is often exclusively investigated through meteorological variables and human-biometeorological indices. Yet, studies on perceived thermal comfort are scarce. As thermal comfort is a property of human perception of the thermal environment, this knowledge is crucial for understanding the relationship between green spaces and thermal comfort. We investigated inhabitants' long-term perception of thermal comfort on warm summer days in three Dutch cities by means of questionnaires. Additionally, we examined the daytime cooling effect of green spaces in Utrecht, in order to find physical evidence to verify thermal comfort perception. To this end we used bicycles equipped with micrometeorological sensors. We compared thermal conditions of 13 parks with thermal conditions in the city centre and in the open grassland outside the city. And we analysed dependences between thermal conditions and spatial variables of parks (size, tree canopy, upwind vegetation cover). Our results demonstrate that green infrastructure improves generally perceived thermal comfort. People evaluated green urban spaces as the most thermally comfortable spaces which was in line with the physical thermal investigations. Physiological equivalent temperature (PET) in parks on average was 1.9 K lower than in the city centre and 5 K lower than in the surrounding grasslands during the hottest period of the day. Thermal variance between parks was significantly influenced by tree canopy cover (mean radiant temperature p = 0.00005) and upwind vegetation cover (air temperature p = 0.013), not significantly for park size. •Green environments are rated as more thermally comfortable than water and built environments.•Perceived thermal comfort in urban green areas fits objective thermal environment.•PET of parks was −1.9 K compared to city centre and −5 K compared to open grassland outside the city.•10% tree cover in a park lowers mean radiant temperature about 3.2 K.•Green cover in upwind urban areas significantly influences air temperature of parks (p = 0.013).